Simultaneous RP-HPLC Determination of Chlorpheniramine Maleate and Paracetamol in Pharmaceutical Formulations - Alwan, Dhilal; AL-SAMARRAYYI, Khalaf F. (Journal of Pharmacology and Drug Development, 2026)
A reliable, rapid, and economical analytical method is required for the quality control of pharmaceutical preparations containing chlorphenamine maleate (CPM) and paracetamol (PCM). This study aimed to develop and validate a reversed-phase high-performance liquid chromatography (HPLC) method for the simultaneous determination and separation of these two common drugs. The chromatographic separation was performed on a C18 column (250×4.6 mm, 5 µm) using an isocratic mobile phase of phosphate buffer (pH 6), water, acetonitrile, and ethanol (70:15:15 v/v) at a flow rate of 0.8 ml/min. Detection was performed using a UV-Vis detector set at 228 nm. The method was validated for both pure substances and pharmaceutical preparations in accordance with standard guidelines, assessing linearity, accuracy, detection limit (LOD), and quantification limit (LOQ). The method successfully separated CPM and PCM with retention times of 3.2 min and 5.3 min, respectively, resulting in a total analysis time of less than 10 minutes. The method demonstrated excellent linearity over concentration ranges of 10-120 µg/mL for CPM (R² =1) and 10-110 µg/mL for PCM (R² = 0.9999). It showed high accuracy and reliability. The LOD was 0.06 µg/mL for CPM and 0.27 µg/mL for PCM, while the LOQ was 0.18 µg/mL for CPM and 0.82 µg/mL for PCM. The developed HPLC method is rapid, sensitive, precise, and economical. It is therefore suitable for routine quality control analysis and for the simultaneous quantification of chlorphenamine maleate and paracetamol in combined pharmaceutical dosage forms.